2003
DOI: 10.2519/jospt.2003.33.8.455
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Assisted Capsular Shrinkage of the Glenohumeral Joint in Overhead Athletes: A 15- to 47-Month Follow-up

Abstract: Study Design: Descriptive postoperative follow-up research. Objectives: The purpose of this investigation was to describe the return-to-competition rate and functional outcome of overhead athletes following arthroscopic thermal-assisted capsular shrinkage (TACS).Background: Traditional open procedures to correct instability in overhead athletes, such as capsulolabral repairs and capsular shifts, have produced less-than-favorable results, which have led to the development of TACS. Currently there are no long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
(108 reference statements)
1
22
1
Order By: Relevance
“…Our rehabilitation program is based on the clinical experience and outcomes observed in more than 300 patients treated with TACS between 1997 and 1999. 43 Ellenbecker and Mattalino 13 provide an overview of their surgical approach and rehabilitation program for 20 patients with unidirectional shoulder instability who were treated using thermal capsulorrhaphy (capsular shrinkage). The authors note that arthroscopic Bankart repairs and capsular shifts were performed concomitantly on an undocumented number of patients at the time of surgery.…”
Section: Rehabilitation Following Thermal-assisted Capsular Shrinkagementioning
confidence: 99%
“…Our rehabilitation program is based on the clinical experience and outcomes observed in more than 300 patients treated with TACS between 1997 and 1999. 43 Ellenbecker and Mattalino 13 provide an overview of their surgical approach and rehabilitation program for 20 patients with unidirectional shoulder instability who were treated using thermal capsulorrhaphy (capsular shrinkage). The authors note that arthroscopic Bankart repairs and capsular shifts were performed concomitantly on an undocumented number of patients at the time of surgery.…”
Section: Rehabilitation Following Thermal-assisted Capsular Shrinkagementioning
confidence: 99%
“…2,3,14,39,45,51,53,65 At our center, Reinold et al 43 reported that 87% of athletes undergoing TACS with concomitant debridement of a SLAP lesion and 84% of athletes with a concomitant SLAP repair returned to competition with good to excellent outcomes using the Modified Athletic Shoulder Outcome Scale.…”
Section: Operative Slap Repair Surgical Techniquementioning
confidence: 99%
“…Pagnani et al 38 found that a complete lesion of the superior portion of the labrum large enough to destabilize the insertion of the biceps was associated with significant increases in anterior-posterior and superior-inferior glenohumeral translation. Reinold et al 43 reported that in a series of 130 overhead athletes with symptomatic hyper laxity undergoing thermal-assisted capsular shrinkage of the glenohumeral joint (TACS), 69% exhibited superior labral degeneration, while 35% had type II SLAP lesions. Furthermore, Pagnani et al 38 reported that the presence of a simulated SLAP lesion in 7 cadaveric shoulders resulted in a 6-mm increase in anterior glenohumeral translation.…”
Section: Pathomechanics Of Slap Lesionsmentioning
confidence: 99%
See 2 more Smart Citations